Effect of shot peening on augmenting the thermo-fluid characteristic of a concentric tube water-to-air counter flow heat exchanger. (June 2021) - Poongavanam, Ganeshkumar; Kim, Sung Chul
Abstract: The current work focuses on heat transfer and pressure drop performance and determines the thermal enhancement factor in a concentric tube heat exchanger (HEX), whereby the external profile of the copper inner tube is modified via shot peening. The Reynolds number of the water-side varied from 6000 to 12, 000 and the water temperature varied from 60 to 80 °C. The cold air mass flow rate was maintained at approximately 0.01 kg/s. The Nusselt number of a shot-peened surface HEX was improved by nearly 25.78%, compared with the normal copper tube HEX, where the water inlet temperature and Re were 80 °C and 10, 000, respectively. The test outcomes displayed that the increase in surface roughness induces the rise in HTFs turbulence and, successively, an augmentation of Nusselt number. The shot peening process breaks the thickness of the viscid sublayer and it creates the local wall turbulence owing to flow separation and reattachment between the grain particles, which enhances the heat transfer to a considerable amount. The friction factor increased up to 26.82% when Re was 6000 and reduced as Re increased. The thermal enhancement factors were in the range 1.007–1.19 for surface roughness of 6.41 μm.